2012
DOI: 10.4314/gjass.v11i1.1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the influence of heavy metals on soil and crops growing within quarry environment at Akamkpa, Cross River State, Nigeria

Abstract: A comparative study of the influence of heavy metals on soils and crops grown within quarry environment at Akamkpa, Cross River State was conducted in 2009 year. The study area was delineated into3 zones P1, P11, P111 based on the intensity of exposure to tailings, wind speed, wind direction and distance from the quarry. The selected sample distances were (0km, 1km and 3km as control). Soil sample with the depth of (0-15cm), cassava leaves and, fluted pumpkin leaves were collected separately from each of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…The higher concentrations of toxic metals recorded in sampling positions within the quarry site con rm the relationship between metal concentrations and distance from the quarry, which is in good agreement with the report of Ekpo et al (2012).…”
Section: Physiochemical Analysis Of Soil and Water Samplessupporting
confidence: 89%
“…The higher concentrations of toxic metals recorded in sampling positions within the quarry site con rm the relationship between metal concentrations and distance from the quarry, which is in good agreement with the report of Ekpo et al (2012).…”
Section: Physiochemical Analysis Of Soil and Water Samplessupporting
confidence: 89%
“…However, with such a level of mechanical exploration of the mineral deposits in the area, the environmental and health consequences may have been considered a matter of concern. Quarrying activity provides a large tone of chippings of various sizes, as well as accompanying toxic wastes that affect both the environment and humans (Ekpo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Shakir and Mohamed (2013) stated that quarrying has resulted in an increase in infrastructural and mineral resource development in several regions.However, Moibi (2007) stated that quarrying causes soil compaction, landscape degradation, soil erosion, and loss of vegetation and soil fauna. Similarly, Ekpo et al (2012) enumerated the destruction of wildlife and biodiversity, loss of fertile soil, air and water pollution, degradation of farmland, impairment of human health, forced pollution migration, and damage to aquatic ecosystems as negative impacts of quarrying on the environment. Several studies (Ekpo et al, 2012;Ezenwa et al, 2014 andTiimub et al, 2015;Nwogha et al, 2017) have reported increase in heavy metal content of soil and plant because of quarrying activities.…”
Section: Introductionmentioning
confidence: 99%
“…The bioaccumulation of heavy elements varies according to species, ages, and organisms [6]. Active vital organs are the organs in which most heavy metals accumulate, such as the liver, kidneys, and gills [7,8]. The current study aimed to study the accumulation of heavy elements (cadmium, copper and zinc), in three tissues of the grass carp fish (gills, muscles and viscera), with a study of the concentrations of elements (cadmium, copper and zinc) in general water and sediment.…”
Section: Introductionmentioning
confidence: 99%